2010
DOI: 10.1104/pp.110.161109
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Acts Downstream of Auxin to Trigger Root Ferric-Chelate Reductase Activity in Response to Iron Deficiency in Arabidopsis      

Abstract: In response to iron (Fe) deficiency, dicots employ a reduction-based mechanism by inducing ferric-chelate reductase (FCR) at the root plasma membrane to enhance Fe uptake. However, the signal pathway leading to FCR induction is still unclear. Here, we found that the Fe-deficiency-induced increase of auxin and nitric oxide (NO) levels in wild-type Arabidopsis (Arabidopsis thaliana) was accompanied by up-regulation of root FCR activity and the expression of the basic helix-loop-helix transcription factor (FIT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
322
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(346 citation statements)
references
References 53 publications
20
322
2
2
Order By: Relevance
“…Increased NO production in various plant species has been widely observed in response to nutrient deficiency in general (Chen et al, 2010b) and P deficiency in particular . Interestingly, in this study, we found that NO is involved in the P deficiency response in rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased NO production in various plant species has been widely observed in response to nutrient deficiency in general (Chen et al, 2010b) and P deficiency in particular . Interestingly, in this study, we found that NO is involved in the P deficiency response in rice.…”
Section: Discussionmentioning
confidence: 99%
“…; García-Mata and Lamattina, 2001), high temperature in Lucerne, Switzerland, low temperature in tomato (Solanum lycopersicum), wheat, and maize (Cueto et al, 1996); Al toxicity in rice bean (Vigna umbellata; Zhou et al, 2012); Fe deficiency in Arabidopsis (Chen et al, 2010b); and P deficiency in white lupin (Lupinus albus; Meng et al, 2012). NO improves the growth of white lupin under P deficiency through inducing cluster-root development and citrate exudation .…”
mentioning
confidence: 99%
“…Together, these results suggest that 3-O-C10-HL-accelerated polar auxin transport likely contributes to the generation of H 2 O 2 or NO. Auxin has previously been shown to simulate H 2 O 2 or NO generation in cucumber, tomato, and Arabidopsis (Joo et al, 2001;Pagnussat et al, 2003;Chen et al, 2010), but auxin did not stimulate NO generation in a tobacco (Nicotiana tabacum) suspension (Tun et al, 2001), suggesting that this is not a universal mechanism and may be context dependent. Plant alkamide as a lipid signal that acts as an AHL homolog can induce the accumulation of NO and adventitious root development in Arabidopsis (Campos-Cuevas et al, 2008), indicating that plants may have evolved a common mechanism to respond to exogenous AHLs, endogenous NAEs, and alkamide stimulation (Méndez-Bravo et al, 2010;MorquechoContreras et al, 2010).…”
Section: The Cross Talk Of H 2 O 2 No and Cgmp May Mediate 3-o-c10mentioning
confidence: 99%
“…In addition to ethylene, other hormones and signaling substances, such as auxin and nitric oxide (NO), have been involved in the up-regulation of Fe and P acquisition genes [3,4,29,68,[75][76][77][78][79][80][81]. In both deficiencies, the activating effect of auxin, ethylene and NO depend on the Fe or P status of the plants [68,69,75,76], which suggests the existence of additional Fe-and P-related signals acting in conjunction with ethylene, auxin and NO [82].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%